2021
DOI: 10.1101/2021.06.01.446664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PLK1 inhibition selectively kills ARID1A deficient cells through uncoupling of oxygen consumption from ATP production

Abstract: Inhibitors of the mitotic kinase PLK1 yield objective responses in a subset of refractory cancers. However, PLK1 overexpression in cancer does not correlate with drug sensitivity, and the clinical development of PLK1 inhibitors has been hampered by the lack of patient selection marker. Using a high-throughput chemical screen, we discovered that cells deficient for the tumor suppressor ARID1A are highly sensitive to PLK1 inhibition. Interestingly this sensitivity was unrelated to canonical functions of PLK1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In our previous studies, we also demonstrated that PLK1 phosphorylation of phosphatase and tensin homolog (PTEN) causes a tumor-promoting metabolic state, promoting the Warburg effect( 27 ). Although it was indicated that PLK1 also has a potential regulatory role in oxidative phosphorylation (OXPHOS) ( 28, 29 ), details of the underlying mechanisms are still lacking. Compared with normal cells, energy metabolism in cancer cells is dramatically altered, and the role of PLK1 in this process remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we also demonstrated that PLK1 phosphorylation of phosphatase and tensin homolog (PTEN) causes a tumor-promoting metabolic state, promoting the Warburg effect( 27 ). Although it was indicated that PLK1 also has a potential regulatory role in oxidative phosphorylation (OXPHOS) ( 28, 29 ), details of the underlying mechanisms are still lacking. Compared with normal cells, energy metabolism in cancer cells is dramatically altered, and the role of PLK1 in this process remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%